25 years after Dolly: Update on long‐term effects of embryo biotechnologies. Issue 4 (7th February 2023) - Chavatte‐Palmer, Pascale; De Schauwer, Catharina
Abstract: Since the announcement of the birth of Dolly, the world's first mammal produced by cloning, it was demonstrated for the first time that somatic cells could be reprogrammed to produce a whole individual. This represented a considerable change in paradigm in the field of embryo technologies both in humans and animals which led to an intense burst of research on nuclear transfer but also on the establishment of pluripotency and the directed edition of the genome. As such, induced pluripotent cells and gene editing tools, the best known being CRISPR‐Cas9, are now available to the scientific community. Nevertheless, cloning was associated with important developmental abnormalities in a variable proportion of pregnancies, raising concern about the long‐term effects of embryo technologies at a time when the concept of the developmental origins of health and disease had emerged, together with a better understanding of the underlying epigenetic modifications. The focus of this article is to review current knowledge on long‐term effects of artificial reproduction technologies in mammals, leading to globally reassuring information although differences are present and caution remains necessary taking the current increasing number of in vitro‐produced ruminant and equine embryos into account and their potential intergenerational consequences.